Youth and their families a guide to treating adolescent substance use through family systems therapy - Laser-Maira, Julie Anne; Wallis, Darin; (Psychologist) Blair, David; Castro, Orion; Conger, Jason; Echevarria, Jamie Blair (New York Oxford University Press, 2019)
In this text we offer an expanded view of the process of therapy and a specific focus on the relationship between therapists, adolescents, families, communities, and substance use. Family Systems Therapy (FST) is not a technique, it is an overarching conceptual framework that views the system as the client. Each client system is unique and each member of the system is believed to be doing what makes sense to them in their given context. Problems that bring individuals into treatment are seen as contextual. If the client system accepts the therapist as a member, the context, within which the problem is maintained, has been changed. By changing the system, change in the individual occurs. Whether or not change is positive or negative is relative and uncertain, but change is inevitable. This is a book written by experienced practitioners and teachers for new and developing practitioners. It is our hope to widen the lens for students and teachers and offer them practice-based approaches to add to their research based teaching. Given the integrative theme of this work, we believe that this text will be useful for students and teachers in graduate programs of Social Work, Marriage and Family Therapy, Professional Counseling, Psychology, and Addiction Counseling. Family Systems Therapy (FST), Family Therapy, Substance Abuse, Adolescent Substance Abuse, Systems Theory"--
Includes bibliographical references and index.
Keywords: Systemic therapy (Family therapy); Drug addiction -- Treatment